2008 Economic Crisis Analysis: The Macroeconomic Approach - Kamran Golmohammadpoor Azar (ZBW - Leibniz Information Centre for Economics; ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2011)
Recent economic crisis started from the American Housing. In 2005, the price of housing started to grow and for gaining more profit, the banks inclined to housing and provided applicants with lots of facilities. With the burst of price bubbles, intense reduction of prices occurred in the housing market and the loan recipients did not have any motives to repay their loans. Therefore, the credit- providing and official organs that had given lots of facilities to the housing sector faced crisis. This recession rapidly spread to other economic sectors and shortly infected Europe and Japan, and also influenced other countries with respect to their dependence on America's economy. This paper, with an approach to macroeconomics and IS-LM model, analyzes the recent crisis.
Conference: International Students Conference on Economics and Finance, Albania
Keywords: 330; Economic Crisis; Macroeconomics; IS-LM Model; America's Economy; Economic Crisis; Makroökonomik; IS-LM-Diagramm; USA